Water and the Course of Empire in North Africa - Knight, Melvin M. (Quarterly Journal of Economics, 1928)
I. The Rise and Fall of Material Culture. Population, cultivated area, and wealth have swelled and dwindled almost rhythmically for thousands of years — the moving frontier of settled agriculture. — II. Rainfall and Cultivated Area. Relation of topography to rainfall and cost of transport by zones, 48. — Significance of the alternate fallow year, 53. — Cereal and olive production the one index of economic development applicable to all periods, 54. — Extent of the economically valuable area. The change since ancient times has been economic, not geographic, 56. — III. Irrigation. Irrigation important, not so much for itself as because of its effects upon the dry-farming area. Evidence from ruins that climate has not basically changed, 58. — Ancient and modern dry-farming similar, 60. — Limited resources of North Africa in irrigation water, 65. — IV. Soil Exhaustion. Soil exhaustion rather an effect or accompaniment of economic decay than a cause, 68. — Some damage from erosion and deforestation, but this less important than commercial, social, and technical changes, 70. — V. Population and its Economic Basis. Growth of Algerian population during the past century. Professor Pearl over emphasizes war-losses, under emphasizes drought periods; but his results are extremely significant, 71. — Algeria a liability to France during the first half-century of fumbling. Followed by a half-century of progress under policies built upon knowledge of North African geography, 74. — VI. The Economics of Empire. Agricultural and administrative policies under which North Africa has prospered roughly similar in all ages, but the differences in detail are important, 79. — "Arabization" has been mainly social and economic, not biological, 82. — Economic significance of Roman and modern frontiers: the camel, the railway, and the motorcar, 83. — "Environmental resistance, " 85. — Can North Africa be a self-supporting or self-governing economic unit? 86. — The benefits of "imperialism, " 87.